Suffocating Phytoplankton, Suffocating Waters—Red Tides and Anoxia - Pitcher, Grant C.; Probyn, Trevor A. (Frontiers in Marine Science, 2016)
The dynamics of O2 depletion in exceptional dinoflagellate blooms, often referred to as red tides or harmful algal blooms (HABs), was investigated in St Helena Bay in the southern Benguela upwelling system in 2013. The transition to bloom decay and anoxia was examined through determination of O2-based productivity and respiration rates. Changes in O2 concentrations in relation to bloom metabolism were tracked by fast response optical sensors following incubation of red tide waters in large volume light-and-dark polycarbonate carboys. Concurrent measurements of nutrients and nutrient uptake rates served to assess the role of nutrient stressors in community metabolism and bloom mortality. The estimates of community productivity and respiration are among the highest values recorded. Nutrient concentrations were found to be low and were unlikely to meet the demands of the bloom as dictated by the rates of nutrient uptake. Ratios of community respiration to gross production were particularly high ranging from 0.6 – 0.73 and are considered to be a function of the inherently high cellular respiration rates of dinoflagellates. Nighttime community respiration was shown to be capable of removing as much as 17.34 ml O2 l-1 from surface waters. These exceptional rates of O2 utilization are likely in some cases to exceed the rate of O2 replenishment via air-water exchange thereby leading overnight to conditions of anoxia. These conditions of nighttime anoxia and nutrient starvation are likely triggers of cell death and bloom mortality further fueling the microbial foodweb and consumption of O2.